2020
DOI: 10.2174/1570159x18666200914161231
|View full text |Cite
|
Sign up to set email alerts
|

The Updated Role of the Blood Brain Barrier in Subarachnoid Hemorrhage: From Basic and Clinical Studies

Abstract: : Subarachnoid hemorrhage (SAH) is a type of hemorrhagic stroke associated with high mortality and morbidity. The blood-brain-barrier (BBB) is a structure consisting primarily of cerebral microvascular endothelial cells, end feet of astrocytes, extracellular matrix, and pericytes. Post-SAH pathophysiology included early brain injury and delayed cerebral ischemia. BBB disruption was a critical mechanism of early brain injury, and was associated with other pathophysiological events. These pathophysiological eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…Furthermore, we found a significant positive correlation between serum and CSF MIF levels during EP d1−4 (Figure 1B), possibly indicating that intrathecal MIF release could be involved in the acute elevation of circulating MIF after aSAH. Thus, assuming a physiological serum concentration of 6-10 ng/ml (17,28), a pathological CSF concentration of 30 ng/ml, and a 1:10 dilution after CSF flow into venous blood (30), the early serum levels of 12.2 [8.7-16.4] ng/ml we observed could well be accounted for by CSF-related changes of MIF concentrations in blood, especially given that early impairments of blood-brain-and blood-CSF-barrier are well-known features of aSAH (31,32), which could be further aggravated by MIF itself (33). The fact that after stratification based on outcome, a significant correlation was only observed in patients with poor clinical outcome (as shown in the Supplementary material) is in line with this assumption, since early blood-brain-barrier dysfunction has been shown to predict neurological outcomes after aSAH (34).…”
Section: Changes In Systemic Mif Levels After Asahmentioning
confidence: 69%
“…Furthermore, we found a significant positive correlation between serum and CSF MIF levels during EP d1−4 (Figure 1B), possibly indicating that intrathecal MIF release could be involved in the acute elevation of circulating MIF after aSAH. Thus, assuming a physiological serum concentration of 6-10 ng/ml (17,28), a pathological CSF concentration of 30 ng/ml, and a 1:10 dilution after CSF flow into venous blood (30), the early serum levels of 12.2 [8.7-16.4] ng/ml we observed could well be accounted for by CSF-related changes of MIF concentrations in blood, especially given that early impairments of blood-brain-and blood-CSF-barrier are well-known features of aSAH (31,32), which could be further aggravated by MIF itself (33). The fact that after stratification based on outcome, a significant correlation was only observed in patients with poor clinical outcome (as shown in the Supplementary material) is in line with this assumption, since early blood-brain-barrier dysfunction has been shown to predict neurological outcomes after aSAH (34).…”
Section: Changes In Systemic Mif Levels After Asahmentioning
confidence: 69%
“…20 Besides, both acute and chronic pathological changes after SAH are associated with the CSF dynamic disorder that involves CSF production, movement, and drainage. A plethora of studies report pathological impairment found in the choroid plexus, 82 BBB, 83 arachnoid granulations, 84 lymphatic, 85 and glymphatic system, 17 which may be related to post-SAH blood clearance. (Figure 3)…”
Section: Csf Dynamics After Sahmentioning
confidence: 99%
“…One of the critical mechanisms of early brain injury is the disruption of the blood-brain barrier (BBB), a structure that primarily consist of cerebral microvascular endothelial cells, astrocytic endfeet, an extracellular matrix, and pericytes [7]. Loss of BBB integrity results in the direct exposure of the brain tissues to neurotoxic blood contents and immune cells, which leads to secondary brain insults, including inflammation and oxidative stress, as well as other cascades [8].…”
Section: Introductionmentioning
confidence: 99%